Insulation Structure Design for ±550-kV DC GIS Based on Multiobjective Optimization Algorithm - Zhang, Boya; Tao, Haifei; Li, Yixuan; Li, Xingwen; Nan, Zhenle; Luo, Wei; Zheng, Yao; Wang, Guoli (IEEE transactions on dielectrics and electrical insulation, 2025)
In high-voltage direct current gas-insulated switchgear (HVdc GIS), the problem of surface charge accumulation on insulators has garnered significant attention, limiting the development of dc GIS at high voltage levels. This study proposes an insulation structure optimization method based on a multiobjective optimization method to balance the tangential and normal electric fields on the insulator surface and mitigate local electric stress, achieving efficient and precise GIS insulation structure design. The optimization objectives include the tangential electric field and surface charge density. The study utilizes nondominated sorting genetic algorithm II (NSGA-II) and response surface methodology (RSM) to obtain the optimal structure for the conical insulator and shield of ±550-kV dc GIS. In addition, the study investigates the impact of gap distance on the surface charge and electric field distribution of the insulator. Ultimately, following insulation optimization design criteria, the study achieves the optimal structure and gap distance for ±550-kV GIS, providing crucial insights for the insulation design of HVdc GIS.